6th AIAA Theoretical Fluid Mechanics Conference 2011
DOI: 10.2514/6.2011-3108
|View full text |Cite
|
Sign up to set email alerts
|

Embedded LES Using PANS

Abstract: An embedded LES modelling approach is explored and verified using the PANS (Partially Averaged Navier-Stokes) model as a platform. With the same base model, the turbulence-resolving LES region is embedded by setting the PANS model coefficient to f k < 1 as distinguished from its neighboring RANS region, where f k = 1 is specified. The embedded LES approach is verified in computations of a turbulent channel flow and a turbulent flow over a hump. Emphasis is placed on the impact of turbulent conditions at the RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Investigation on the effect of the domain extent in the spanwise direction was conducted by doubling the spanwise extent of the computations domain. It is confirmed that the domain size is adequate in the baseline configuration and in a previous study 29 it has been concluded that also the spanwise grid resolution is sufficient.…”
Section: Vb Hump Flowsupporting
confidence: 71%
See 2 more Smart Citations
“…Investigation on the effect of the domain extent in the spanwise direction was conducted by doubling the spanwise extent of the computations domain. It is confirmed that the domain size is adequate in the baseline configuration and in a previous study 29 it has been concluded that also the spanwise grid resolution is sufficient.…”
Section: Vb Hump Flowsupporting
confidence: 71%
“…28 The upwinding is used because in Ref. 29 it was found that pure central differencing gave rise to unphysical resolved stresses near the inlet. The…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A blend of the two discretization schemes was motivated by a previous investigation of the hump flow by Davidson and Peng,22 where it was shown that 100% central differencing gave unphysical fluctuations, especially in the interface region. The turbulent transport equations were discretized using a first order hybrid scheme.…”
Section: Ivd Hump Flowmentioning
confidence: 98%
“…where u ′ i,synt denotes anisotropic synthetic fluctuations that were obtained using the same procedure as in [10]. In the present work, contrary to [10], the synthetic fluctuations are scaled with k RAN S /k RAN S,max . The inlet modelled turbulent kinetic energy and its dissipation are computed as [10].…”
Section: Boundary Layer Flowmentioning
confidence: 99%